Plasticity in selection strategies of woodland caribou ( Rangifer tarandus caribou) during winter and calving. - Gustine, David D. (Author); Parker, Katherine (Thesis advisor); University of Northern British Columbia (Degree granting institution) (University of Northern British Columbia, 2005)
Woodland caribou may be an important indicator' or focal species for management agencies because they require large areas to persist and are sensitive to both direct and indirect forms of disturbance. Prior to industrial development in northern regions, it is important to acquire baseline information on areas that are important to local 'herds' as well as to identify physiological and ecological mechanisms of resource selection. I used global positioning system (GPS) data from caribou {Rangifer tarandus caribou), wolves {Canis lupus), and grizzly bears {Ursus arctos), and satellite imagery, resource selection functions, and cause-specific mortality data from 50 caribou neonates to define calving and wintering areas of woodland caribou in northern British Columbia. I identified scale-dependant mechanisms of selection relative to predation risk (calving, summer, winter, and late winter) and forage availability (calving and summer), and energetic costs of movement (winter and late winter) at 2 spatial scales, and quantified the variation in responses to these mechanisms among individual caribou. In all seasons, caribou selected habitats in a hierarchical fashion, and exhibited high variation among individuals. Three unique calving areas, or calving strategies, were defined for the Greater Besa Prophet area; each calving area had different attributes of risk and forage. During calving, spatial separation from areas of high wolf risk was important to parturient females as was access to areas of high vegetative change (i.e., forage quality); animals made trade-off decisions between minimizing the risk of predation and securing forage to address the high nutritional demands of lactation. Calf survival through the first 2 months of life ranged from 54% in 2002 to 79% in 2003. A total of 19 of 50 neonates died during the summers, of which 17 were by predation: wolverines (age of calves <14 d) and wolves (age of calves >18 d) each killed 5 calves. Movements away from calving sites (>1 km) peaked during the third ...